JOAQUIN ALVARADO GARCIA (1954-1997): RANGER FOREVER (Biocenosis, 2014)
This paper presents the biography of Joaquin Garcia Alvarado, a very important person in the history of the Cabo Blanco Nature Reserve and other national parks where he served as rangers. It is notable for its vision, which led him to countries like the Netherlands and Denmark in search of funds to invest in the conservation of parks and other protected areas of the country. His early death cut short his significant work on behalf of the National System of Conservation Areas and Costa Rican natural wealth.
Keywords: Biography; Costa Rica; Biodiversity